(untitled) (Asian Business Research, 2017)
This research examines the past and present of innovative gaming. We explore the events and innovations that have led to the success of Pokémon Go and raise issues and questions that invite marketers to further delve into an agenda of research that would be truly valuable to practitioners and academicians alike.